(untitled) (PROKLA. Journal of Critical Social Science, 1998)
The article contributes to a feminist analytics that allows us to reconceptualize major features of today’s global economy in a manner that captures strategic instantiations of gendering and formal and operational openings that make women visible. Two strategic research sites are specified: the unbundling of exclusive territoriality and the unbundling of sovereignty under the impact of globalization.